Enhancing Student’ Speaking Ability By Using Student’ Centered Learning At Faculty Of Teacher Training And Education Of Tridinanti University Palembang - Gaya Tridinanti (Jurnal Didascein Bahasa, 2015)
Abstract : The problem of this study was to find out whether it is effective or not to use students’ centered learning strategy in enhancing students’ speaking ability. It aims to find out the effectiveness of students’ centered learning method to enhance students’ speaking ability. The population was all of the students of Faculty of Teacher Training and Education of Tridinanti University Palembang in academic year 2013-2014. They were 32 students and taken by using random sampling. The method was pre-experimental method by using pre-test and the post-test design. The data were obtained by means of the test, the results were analyzed through the match t-test calculation. Based on the finding, the writer found that the average score in the pre-test was 62.97, and the average score in the post-test was 75.62. From the matched t-test calculation, the writer got that t-obtained was 4.85. It showed that t-obtained was higher than critical value (1.684) . It can be concluded that it was effective to use students’ centered learning strategy in enhancing student’ speaking ability at Faculty of Teacher Training and Education of Tridinanti University.Keywords : speaking ability, students’ centered learning.